2012
DOI: 10.1055/s-0032-1306325
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intervention May Prevent Depression

Abstract: Physical activity is an effective component of depression management. However, the mechanisms by which exercise affects behavioral disorders remain unclear. The present study was conducted to investigate mechanisms by which voluntary exercise ameliorates depression. Plasma cortisol levels and hippocampal monoamine neurotransmitters were measured. Chronic mild stress (CMS) was used to induce depression in a rat model. The rats were allowed to swim for 10 weeks as part of their exercise treatment. Depressive beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 9 publications
1
19
0
6
Order By: Relevance
“…The present observations are partially consistent with previous studies that examined the effects of a physical activity on the serum levels of serotonin (He et al, 2012). Also significant decrease in serum leptin, body weight and BMI values in RES group were reviewed in previous studies (Akbarpour, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The present observations are partially consistent with previous studies that examined the effects of a physical activity on the serum levels of serotonin (He et al, 2012). Also significant decrease in serum leptin, body weight and BMI values in RES group were reviewed in previous studies (Akbarpour, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Regular mild to moderate exercise seems to improve the maternal perception of fetal movements through different mechanisms affecting both the mothers and the fetuses. Exercise results in increased serum cortisol, hippocampal dopamine and serotonin levels, and these changes lead to increased mood and mental alertness [17, 20], which can improve the maternal perception of fetal movements. A Canadian study showed that pregnant women who exercise during pregnancy experience significant decreases in depression, anger, tension, fatigue and anxiety [21], the factors which have been shown to be associated with decreased perception of fetal movements [12, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…166,167 In rats that swam (n=18) 5 days a week for 10 weeks (typically 30 minutes per day), exercise was associated with increased hippocampal levels of serotonin and norepinephrine 168 – two neurotransmitters that have been implicated in modulation of anxiety, depression, and sleep. 156,169171 In regard to the potential for improved cognition, 172 animal work indicates that serotonin is necessary in order to achieve exercise-induced neurogenesis in the hippocampus (n=30 per group).…”
Section: Potential Mechanisms Of Action Of Exercise On Mood Cognitiomentioning
confidence: 99%